The energy-based scaling of a thin current sheet Case study - Sasunov, Yu L (Geophysical research letters, 2015)
The influence of average plasma energy E~ on the half thickness ℓ of a thin current sheet (TCS) is investigated for three cases of TCSs crossings. The value of ℓ was estimated from the magnetic field data by means of Cluster observations. The obtained scaling values for TCSs, Z~=ℓ/ρT, where ρT is the thermal Larmor radius, were compared with the scaling Zμ=22E~/T, where E~ and T are the average plasma energy and the temperature of plasma, which assumes a specific dynamics (conservation of magnetic flux through the trajectory segment) of the current carriers. The comparison of Z~ and Zμ shows a good agreement